Interethnic contact and its influence on ethnic prejudices throughout childhood - Solbes, Irene; Callejas, Carolina; Rodríguez, Purificación; Lago, María Oliva (Anales de Psicología / Annals of Psychology, 2011)
We studied attitudes of 956 Spanish children from 6 to 12 years old toward different potential classmates who belonged to two ethnic groups (White / Black). Participants attended two different school contexts: ethnically heterogeneous classrooms versus homogeneous contexts. With this aim, we have designed different tasks that allowed us to study children´s preferences for sharing different activities, as well as the possible attribution of adjectives (stereotypes) associated whit this two different types of potential classmates. Results showed significant ethnic prejudices in the whole sample, displaying a trend of rejection toward Black children for sharing different activities (such as studying or playing), while White ones were most likely chosen. Black targets were also associated with negative stereotypes, whereas White targets were more often associated with positives attributes. Bias slightly decreased as the age of the participants increased, as showed in most of the previous studies in the field. Effect of classroom context (ethnically heterogeneous / homogeneous) had an influence on the magnitude of the ethnic prejudices, but in the opposite sense proposed by Allport´s (1954) contact hypothesis. Children attending heterogeneous contexts showed stronger and more persistent bias than children attending homogeneous centers: daily interethnic contact with ethnic minority children does not reduce per se ethnic prejudices during childhood.